DESAIN DAN SINTESIS SENYAWA ACES (ANALOG CURCUMIN SERIES) DENGAN METODE SOLID PHASE REACTION SEBAGAI SENYAWA ANTIKANKER POTEN DENGAN MEKANISME MENGHAMBAT PROTEIN NF-kB - Monica Sabrina Widiapranolo; Eva Mayangsari; Venny Valeria; Jeffry Julianus (Sanata Dharma University, 2013)
Abstract: Analog of curcumin in forms of enone and dienone aromatic is known for their activityas an NF-?B inhibitor. In this study, will be synthesize 2-(4'-N, N-dimethylamino benzilidine)cyclohexane-1,3-dione as an analog that predicted has an activity as an NF-?B inhibitor. Thisresearch was conducted based on the crossed aldol condensation reaction by reacting 3 mmole pN,N-dimethylamino benzaldehide and 6 mmole cyclohexane-1,3-dione with hydrochloric acid asthe catalyst using solid phase reaction method. Based on computational analysis, 2-(4'-N,Ndimethylamino benzilidine) cyclohexane-1,3-dione showed a better interaction with NF-?Bprotein with PLANTSPLP score was -69,7895. The outcome of the reaction was yellow coloredpowder, no odor and soluble in hydrochloric acid 3N. The yield value was 78.8%. Liquidchromatography showed 100% purity. The melting point range was 237.5-240.3C. The resultsof structure elucidation by 1H-NMR, infrared and mass spectroscopy tests indicated thecompound was 2-(4-(dimetilamino)benzilidena)-4-(3-oksosiklohex-1-enil) sikloheksana-1,3-dion.Key words: 2-(4'-N, N-dimethylamino benzilidine) cyclohexane-1,3-dione, crossed aldolcondensation, solid phase reaction.